Sketch of the recent discoveries on the northern coast of America by Daptain McClintock R.N. in search of Sir John Franklin. - Wyld, James, 1812-1887. http://id.loc.gov/authorities/names/n83049169 http://viaf.org/viaf/sourceID/LC|n83049169 (UM Clark Library Maps, 1859)
Relief shown by hachures.; Includes inset map showing the probable route of the Franklin Expedition.; Shows the routes of other search expeditions and places where where relics of the Franklin Expedition have been found. 1 map : hand col. 48 x 36 cm., folded in cover 17 x 10 cm.